A Defense of the ‘Sterility Objection’ to the New Natural Lawyers’ Argument Against Same-Sex Marriage - Anderson, Erik A. (2013)
The “new natural lawyers” (NNLs) are a prolific group of philosophers, theologians, and political theorists that includes John Finnis, Robert George, Patrick Lee, Gerard Bradley, and Germain Grisez, among others. These thinkers have devoted themselves to developing and defending a traditional sexual ethic according to which homosexual sexual acts are immoral per se and marriage ought to remain an exclusively heterosexual institution. The sterility objection holds that the NNLs are guilty of making an arbitrary and irrational distinction between same-sex couples and sterile heterosexual couples. The NNLs believe that it is a necessary condition for two people’s being morally and legally entitled to get married that they be able to perform sexual acts that are “suited to procreating.” But sterile heterosexual couples are incapable of performing such acts. Therefore, it should follow from the NNLs’ own premises that sterile heterosexual couples are not entitled to marry. But the NNLs do not draw this conclusion. Instead, they maintain that sterile heterosexuals can marry while denying that the same is true of same-sex couples. The sterility objection claims the NNLs are being inconsistent in treating the two kinds of couples differently. Although the sterility objection has been endorsed by recent critics, I don’t think it has yet been adequately defended. The NNLs have responded by arguing that there is a sense in which the sex acts of sterile heterosexual couples are as suited to reproduction as those of fertile heterosexuals. Thus they maintain that the distinction they draw between the two kinds of couple has a rational basis. A successful defense of the sterility objection must show that this response on the part of the NNLs fails. Such is the task I undertake in this paper. I argue that the NNLs’ response fails because acts of penile-vaginal intercourse between sterile heterosexuals lack the actual causal power to produce conception that sexual acts need to be considered truly reproductive, and because their assumption that penile-vaginal intercourse always functions reproductively is bad biology.
Keywords: Gay rights; Sexual ethics; Same-sex marriage; new natural law; Homosexuality